2022
DOI: 10.3390/ijerph191912782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Denmark’s New Tobacco Control Act on Young People’s Use of Nicotine Products: A Study Protocol of the §SMOKE Study

Abstract: (1) Background: In December 2020, a broad majority of political parties in Denmark agreed on a new tobacco control act. In addition, price increases on tobacco in 2020 and 2022 became part of the Danish Finance Act. This study protocol describes the study “§SMOKE–A Study of Tobacco, Behavior, and Regulations” designed to monitor and evaluate the implementation and effect of the new strengthened tobacco control acts. The overall aim is to monitor tobacco use among young people before, during, and after implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…To ensure that essential analyses could be made, including investigating changes in tobacco patterns over the study period as well as subgroup-and stratified analyses, the requested sample size was set to 15,000 respondents. With an expected response rate in this age group at 40%, we invited 37,500 persons to the study [19].…”
Section: Participants and Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that essential analyses could be made, including investigating changes in tobacco patterns over the study period as well as subgroup-and stratified analyses, the requested sample size was set to 15,000 respondents. With an expected response rate in this age group at 40%, we invited 37,500 persons to the study [19].…”
Section: Participants and Sample Sizementioning
confidence: 99%
“…Further, we examined the distribution of responses and non-responses according to region in Denmark and found that the distributions did not markedly differ. The weights ensured representability of the study sample and reduced the impact of non-responses (for more detailed information, see also [19]).…”
Section: Sociodemographic Characteristics and Weighting Proceduresmentioning
confidence: 99%